2020
DOI: 10.1111/avsc.12512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of livestock grazing on plant species diversity vary along a climatic gradient in northeastern Iran

Abstract: Questions: (a) Do patterns of species diversity and composition differ between plots exposed to high vs. low grazing intensity? (b) Do these differences vary among three regions with different climates, representing a gradient from arid to sub-humid conditions? Location: Northeastern Iran. Methods: We compared plots intensively grazed by sheep and goat (HG) to plots with low grazing intensity (LG), across three climatic regions: arid, semi-arid and sub-humid. Species diversity (expressed as Shannon H) was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
5
12
0
Order By: Relevance
“…Ojima and coauthors [ 72 ] found that overgrazing results in the loss of vegetation cover and increased erosion. The low vegetation cover provides low protection from soil erosion and a high risk for degradation [ 13 ] and reduced soil porosity [ 46 , 73 ]. This reduced vegetation cover and the lower plant diversity probably increase the susceptibility of rangelands to the effects of climate change as well [ 37 , 38 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ojima and coauthors [ 72 ] found that overgrazing results in the loss of vegetation cover and increased erosion. The low vegetation cover provides low protection from soil erosion and a high risk for degradation [ 13 ] and reduced soil porosity [ 46 , 73 ]. This reduced vegetation cover and the lower plant diversity probably increase the susceptibility of rangelands to the effects of climate change as well [ 37 , 38 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy grazing directly changes the floristic composition of plant communities selectively, changing the structure and composition of communities at the expense of palatable species [ 43 , 44 ], and may also indirectly modify the outcome of competitive interaction by changing light availability [ 45 ]. The impact of grazing intensity on plant diversity varies along the precipitation gradient [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial degradation of these valuable natural ecosystems is occurring due to overpopulation, overexploitation, and unsustainable development (United Nations Development Program, 2006). Furthermore, the unsustainable use of rangelands is being intensified by climate change (Rahmanian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing is a key biotic stress in dry rangelands due to its extensive application and its potential to change the community structure and species composition, and to degrade the ecosystem services (Diaz et al., 2007 ; Jankju, 2016 , Kéfi et al., 2007 ; Li et al, 2013 , Rahmanian et al, 2019 , 2020 ). Previous studies examining the herbivores as main drivers have reported that unattractive, toxic, or thorny plants may induce positive indirect (i.e., grazer‐mediated) effects on palatable herbs, shrubs, or trees (Bakker et al., 2004 ; Callaway et al., 2005 ; Smit et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%